LncRNA KCNQ1OT1 promotes osteogenic differentiation to relieve osteolysis via Wnt/β-catenin activation - Xuren Gao; Jian Ge; Weiyi Li; Wangchen Zhou; Lei Xu (Cell & Bioscience, 2018)
Abstract Background Resveratrol (RSV) has been reported to stimulate osteoblast differentiation in which Wnt/β-catenin signaling pathway played a crucial role. However, whether and how RSV activated Wnt/β-catenin pathway in osteogenic differentiation still remained elusive. Methods In vivo polymethylmethacrylate (PMMA) particle-induced osteolysis (PIO) mouse model and in vitro PMMA particle-stimulated mouse mesenchymal stem cells (mMSCs) experiments were established. Relative expression levels of lncRNA KCNQ1OT1, β-catenin, Runx2, Osterix and osteocalcin were determined using quantitative Real-Time PCR. Western blotting was used to measure β-catenin protein expression. In addition, the alkaline phosphatase activity and mineral deposition level using alizarin red S staining were performed to examine osteogenic differentiation status. The interaction between KCNQ1OT1 and β-catenin was confirmed by RNA pull down assay. Results RSV significantly attenuated PIO in vivo and PMMA-particle inhibition of osteogenic differentiation of mMSCs. Moreover, KCNQ1OT1 exerted the similar function in mMSCs by regulating β-catenin. Further study demonstrated that RSV exerted its effect on osteoblastic differentiation by regulating KCNQ1OT1. Consequently, RSV alleviated PMMA-particle inhibition of osteoblastic differentiation via Wnt/β-catenin pathway activation in vivo and in vitro. Conclusion RSV accelerated osteoblast differentiation by regulating lncRNA KCNQ1OT1 via Wnt/β-catenin pathway activation, indicating the functional role of RSV in modulating osteogenesis.